The lived experience of anxiety and the many facets of pain: A qualitative, arts-based approach - Roberta Lynn Woodgate; Pauline Tennent; Sarah Barriage; Nicole Legras (Canadian Journal of Pain, 2020)
Background: Findings reported in this article emerged from the study titled “Youth’s Voices: Their Lives and Experiences of Living with an Anxiety Disorder.” Though the initial focus of this study was not on the pain experiences of youth living with an anxiety disorder, it became apparent from the very first interviews that pain and suffering was key in the youth lived experience, permeating their everyday lives and impeding their participation and functioning in the world. Aims: The aim of this article is to highlight the ways in which pain is a central experience for young people living with an anxiety disorder. Methods: The study was approached from the qualitative research design of hermeneutic phenomenology. Fifty-eight young people who were living with anxiety disorders and their parents participated in the study. Youth took part in multiple qualitative open-ended interviews and the participatory arts-based method of photovoice. Themes were developed using van Manen’s method of data analysis. Results: The overall theme emerged as “anxiety is very much about pain.” The four subthemes are (1) embodied experience of anxiety: physical pain; (2) a prominent symptom of anxiety: mental–emotional pain; (3) difficult interpersonal relationships: social pain; and (4) articulating their pain. Conclusions: Use of qualitative, arts-based methodologies provided the opportunity and space for youth with anxiety to articulate their multifaceted experience with pain in their own words. This work reinforces the need for use of qualitative approaches to understanding pain experiences in young people.